Combination of heterologous fibrin sealant and bioengineered human embryonic stem cells to improve regeneration following autogenous sciatic nerve grafting repair - Mozafari, Roghayeh; Kyrylenko, Sergiy; Castro, Mateus Vidigal; Ferreira, Rui Seabra [UNESP]; Barraviera, Benedito [UNESP]; Oliveira, Alexandre Leite Rodrigues (Springer Nature, 2018)
Background: Peripheral nerve injury is a worldwide clinical problem, and the preferred surgical method for treating it is the end-to-end neurorrhaphy. When it is not possible due to a large nerve gap, autologous nerve grafting is used. However, these surgical techniques result in nerve regeneration at highly variable degrees. It is thus very important to seek complementary techniques to improve motor and sensory recovery. One promising approach could be cell therapy. Transplantation therapy with human embryonic stem cells (hESCs) is appealing because these cells are pluripotent and can differentiate into specialized cell types and have self-renewal ability. Therefore, the main objective of this study was to find conditions under which functional recovery is improved after sciatic nerve neurorrhaphy. We assumed that hESC, either alone or in combination with heterologous fibrin sealant scaffold, could be used to support regeneration in a mouse model of sciatic nerve injury and repair via autografting with end-to-end neurorrhaphy. Methods: Five millimeters of the sciatic nerve of C57BL/6 J mice were transected off and rotated 180 degrees to simulate an injury, and then stumps were sutured. Next, we applied heterologous fibrin sealant and/or human embryonic stem cells genetically altered to overexpress fibroblast growth factor 2 (FGF2) at the site of the injury. The study was designed to include six experimental groups comprising neurorrhaphy (N), neurorrhaphy + heterologous fibrin sealant (N + F), neurorrhaphy + heterologous fibrin sealant + doxycycline (N + F + D), neurorrhaphy + heterologous fibrin sealant + wild-type hESC (N + F + W), neurorrhaphy + heterologous fibrin sealant + hESC off (N + F + T), and neurorrhaphy + heterologous fibrin sealant + hESC on via doxycycline (N + F + D + T). We evaluated the recovery rate using Catwalk and von Frey functional recovery tests, as well as immunohistochemistry analysis. Results: The experiments indicated that sensory function improved when transgenic hESCs were used. The regeneration of sensory fibers indeed led to increased reflexes, upon stimulation of the paw ipsilateral to the lesion, as seen by von-Frey evaluation, which was supported by immunohistochemistry. Conclusions: Overall, the present data demonstrated that transgenic embryonic stem cells, engineered to overexpress FGF-2 in an inducible fashion, could be employed to support regeneration aiming at the recovery of both motor and sensory functions.
Keywords: FGF2; Fibrin sealant; Human embryonic stem cells; Neurorrhaphy; Sciatic nerve